2021
DOI: 10.1001/jamanetworkopen.2021.27827
|View full text |Cite
|
Sign up to set email alerts
|

Testing Practices, Interpretation, and Diagnostic Evaluation of Iron Deficiency Anemia by US Primary Care Physicians

Abstract: IMPORTANCE Recognition of iron deficiency anemia (IDA) is important to initiate timely evaluation for gastrointestinal tract cancer. Retrospective studies have reported delays in diagnostic evaluation of IDA as a common factor associated with delayed diagnosis of colorectal cancer. OBJECTIVE To assess how US primary care physicians (PCPs) approach testing for anemia, interpret iron laboratory studies, and refer patients with IDA for gastrointestinal endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Hemolytic anemia is present when the reduction in the quantity of RBC is caused by decreased cell lifespan secondary to cell destruction. The causes of hemolytic anemia include immune hemolytic disorders, hemoglobin disorders, RBC enzyme disorders, and RBC membrane disorders [ 1 , 2 ]. Clinical presentation is determined by decreased RBC number and rapid cell turnover metabolic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Hemolytic anemia is present when the reduction in the quantity of RBC is caused by decreased cell lifespan secondary to cell destruction. The causes of hemolytic anemia include immune hemolytic disorders, hemoglobin disorders, RBC enzyme disorders, and RBC membrane disorders [ 1 , 2 ]. Clinical presentation is determined by decreased RBC number and rapid cell turnover metabolic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment of IDA in pregnancy, while relatively straightforward, is often overlooked and not optimally managed by healthcare providers 12 . This is largely because many practitioners lack adequate knowledge on iron repletion and often approach treatment using an excessive use of oral iron, which offers marginal to no benefit with increasing doses, but can cause significant gastrointestinal toxicity 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment of IDA in pregnancy, while relatively straightforward, is often overlooked and not optimally managed by healthcare providers. 12 This is largely because many practitioners lack adequate knowledge on iron repletion and often approach treatment using an excessive use of oral iron, which offers marginal to no benefit with increasing doses, but can cause significant gastrointestinal toxicity. 13,14 In addition, older formulations of intravenous iron that require multiple small doses (e.g., iron sucrose) and ferric gluconate are still being administered as opposed to newer formulations which are more convenient, require a single dose, and have similar safety profiles.…”
mentioning
confidence: 99%
“…Excessive reliance on oral iron can delay effective treatment via intravenous (IV) iron and also lead to significant side effects including dyspepsia and constipation 6 . Observation studies have additionally suggested that physicians have significant knowledge gaps in diagnosing and treating iron deficiency 7 . This is in part due to inequities in the United States healthcare system that have led to an absence of clear consensus guidelines regarding the treatment of iron deficiency and a resultant lack of practice uniformity 8 …”
Section: Introductionmentioning
confidence: 99%
“…6 Observation studies have additionally suggested that physicians have significant knowledge gaps in diagnosing and treating iron deficiency. 7 This is in part due to inequities in the United States healthcare system that have led to an absence of clear consensus guidelines regarding the treatment of iron deficiency and a resultant lack of practice uniformity. 8 In the following sections, we outline the pathophysiology of iron absorption, the available options for oral iron repletion, and potential side effects.…”
Section: Introductionmentioning
confidence: 99%